Integrating STEM into Religious Education: Exploring the Role of University Lecturers in Merging Science, Technology, Engineering, and Mathematics with Faith-Based Pedagogy - Tri Ngudi Wiyatno; Muhammad Zaini El Wahyu; Ainur Rahman; Sarwo Edy (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to evaluate the effectiveness of the STEM (Science, Technology, Engineering, and Mathematics) teaching model employed by religious education lecturers at Pelita Bangsa University. Integrating STEM in religious education is expected to enhance critical thinking, problem-solving skills, and the practical application of knowledge in both professional and everyday contexts. A qualitative research design was used, with data collected through interviews and surveys distributed via Google Forms. Data analysis involved four stages: data reduction, data presentation, verification, and conclusion drawing. The study sample consisted of 13 religious education lecturers from the Primary School Teacher Education (PGSD) Study Program at Pelita Bangsa University, all of whom taught Islamic religious education courses. The findings indicated a marked improvement in students' critical thinking and problem-solving abilities, particularly in their ability to apply technology during the learning process. Furthermore, all survey responses related to lecturers' preparedness and competence in implementing the STEM model showed consistently high ratings. The results suggest that integrating STEM into religious education enhances students' cognitive abilities and technological skills. The high competence and preparedness of the lecturers further support the effectiveness of this approach. This research highlights the potential of STEM-based learning in religious education and emphasizes the importance of lecturer readiness in its successful implementation. The STEM teaching model proves effective in improving students' thinking and problem-solving abilities in religious education at Pelita Bangsa University. The high levels of lecturer competence and preparedness further strengthen the implementation of this approach.